Identification of a T cell surface molecule using a monoclonal antibody produced by TCR/CD3 complex immunization - Kodchakorn Mahasongkram (2018)
© 2015, Allergy and Immunology Society of Thailand. All rights reserved. Background: Several molecules are known to be involved in T-cell activation via the TCR/CD3 complex and while the mechanisms of late T cell signaling have been well characterized, the very early events are still not fully understood. Objective: The aim of this study was to identify yet unknown molecules associated with the TCR/CD3 complex. Results: To identify new molecules associated with the TCR/CD3 complex, a monoclonal antibody termed MT3 was produced by immunoprecipitated beads immunization. Colocalization of the MT3 mAb recognizing molecules with the TCR/CD3 complexes was verified by confocal microscopic analysis. The surface antigen recognized by MT3 antibody was expressed on a subpopulation of CD3+ T cells, and on both CD4+ and CD8+ lymphocytes. The antigen was also expressed on naïve CD4+ T cells and on a subset of memory CD4+ T cells. In contrast, in the CD8 population, the majority of MT3+ cells were found in the naïve population. The MT3 mAb recognizing molecules were also expressed on red blood cells but only in particular subjects. Similar to peripheral blood leukocytes, MT3 mAb recognizing molecules are exclusively expressed on T cell lines. Conclusions: Based on the cellular distribution patterns and confocal microscopic analysis, the MT3 mAb recognizing molecule that we investigated is proposed to be a TCR/CD3 associated molecule and might be involved in the antigen recognition of T cells.